2015
DOI: 10.3171/2015.10.focus15386
|View full text |Cite
|
Sign up to set email alerts
|

Length of hospital stay after craniotomy for tumor: a National Surgical Quality Improvement Program analysis

Abstract: OBJECT Although the length of hospital stay is often used as a measure of quality of care, data evaluating the predictors of extended hospital stay after craniotomy for tumor are limited. The goals of this study were to use multivariate regression to examine which preoperative characteristics and postoperative complications predict a prolonged hospital stay and to assess the impact of length of stay on unplanned hospital readmission. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 69 publications
12
106
3
3
Order By: Relevance
“…Based on previous studies of LOS in the CFBT population, the primary outcome for the LOS model was defined as greater than 7 inpatient days versus less than or equal to 7 inpatient days. 6 According to this definition, patients with extended LOS made up approximately one third of the CFBT population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies of LOS in the CFBT population, the primary outcome for the LOS model was defined as greater than 7 inpatient days versus less than or equal to 7 inpatient days. 6 According to this definition, patients with extended LOS made up approximately one third of the CFBT population.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has demonstrated the existence of racial disparities for these outcomes following CFBT – Curry and colleagues showed that black patients have more non-home discharge after CFBT, 5 while Dasenbrock et al saw that black or Hispanic patients were more likely to have extended LOS (>7 days). 6 We expand on this work in three important ways: (1) we use a novel guided ML ensemble technique to validate findings ascertained using more traditional statistical methods; (2) we compare findings in the NIS CFBT population to the NIS population as a whole to determine whether our findings are system-wide or specific to the CFBT population; and (3) we explore the interplay between discharge disposition and LOS.…”
Section: Introductionmentioning
confidence: 99%
“…Patients enrolled in the NSQIP are followed for 30 days postoperatively, and all complications (among those collected in the NSQIP algorithm) that occurred during this period are recorded; there is no administrative censoring or loss to follow-up of patients entered. The accuracy of data collection by the NSQIP (including cumulative incidence and reasons for readmission) has been externally validated, 84 and this data source has been previously used to evaluate patients undergoing neurosurgical intervention, 4,8,12,14,15,28,29,45,54,83 including spine surgery. 2,6,9,10,25,40,53,59,61,82,91 Our institutional review board has exempted the de-identified NSQIP data set from individual review.…”
Section: Data Sourcementioning
confidence: 99%
“…In the absence of traditional high-level medical evidence (i.e., randomized controlled trials) for outcomes after many neurosurgical procedures, analysis of large prospective registries is becoming increasingly important in determining the exact risks and benefits of surgical intervention [16,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The data are collected by trained surgical reviewers employed at each participating site. The NSQIP dataset has been previously validated [18], and has been used to evaluate outcomes for a variety of neurosurgical procedures [15,16,[18][19][20][21][22][23][24][25][26].…”
Section: Data Sourcementioning
confidence: 99%